Field bioefficacy and residue dynamics of chlorantraniliprole (18.50% sc) in okra (Abelmoschus esculentus) - MAJUMDER, SUJAN; RANI, A T; DIVEKAR, PRATAP A; HALDER, JAYDEEP; PANDEY, K K; BEHERA, T K (The Indian Journal of Agricultural Sciences, 2023)
The okra fruit borer (Earias vittella) and sucking pests are a key limiting factor in okra cultivation due to their severe crop destruction behaviour. An experiment was conducted during 2019–20 to assess the bioefficacy of various new insecticides and persistence of chlorantraniliprole 18.50 sc residues in okra fruits at research farm of ICAR- Indian Institute of Vegetable Research, Varanasi, Uttar Pradesh. Among various treatments, chlorantraniliprole tested at 30 g a.i./ha was reported to be effective in reducing fruit damage by E. vittella (96%), as well as sucking pests infestation (87.81–1100%) with a significantly higher marketable fruit yield (8.88 t/ha) recorded under open field situations. Ethyl acetate was used to extract the chlorantraniliprole contaminants from the okra fruit matrix, and PSA and magnesium sulphate were used to clean up the matrix. The estimate for the limit of quantification (LOQ) was 0.01 mg/kg, and the average percent recoveries ranged from 83.67–89.00. The half-life was estimated 1.72 days. Based on the field bioefficacy against insect pests and residue status in okra fruits, it can be concluded that the chlorantraniliprole 30 g a.i./ha can be utilized in the okra ecosystem to successfully manage the sucking pest complex and fruit borer without posing any health risks to consumers.